A visit to Australia - Mather, Charis, 1999- (Minneapolis, Minnesota : Bearport Publishing, 2023)
Take a trip to Australia! Start in the city of Sydney, where you'll find an impressive bridge and a famous opera house. Then, head into nature to see the beautiful Uluru rock formation and the Great Barrier Reef. And don't forget to say hi to the kangaroos and koalas! Learn all about Australia as you explore the country through this fun and engaging book.
Country to country -- Today's trip is to Australia! -- Sydney -- Uluru -- Aboriginal traditions -- Aboriginal art -- Great Barrier Reef -- Animals -- Lake Hillier -- Before you go.
Includes index.
3.8
K-3
710L
Keywords: Australia -- Juvenile literature; Australia -- Social life and customs -- Juvenile literature; Australia; Australia -- Social life and customs